Die Förderung demokratischer Grundhaltungen als Teil professioneller Kompetenz angehender Lehrpersonen: Darstellung eines Forschungsvorhabens - Wehde, Janis; Bloh, Bea

Salutogenes Leitungshandeln. Ein Ansatz zur Gesundheitsförderung und Qualitätsentwicklung in der Schule. - Bloh, Bea; Wehde, Janis (Lernende Schule)

Präkonzepte von Grundschulkindern zur Zeitzeug*innenbefragung – Eine empirische Untersuchung zu Kompetenzen historischen Denkens - Diederich, Julia
Die Zeitzeug*innenbefragung gilt als kindgemäßer Zugang zur Alltags- und Zeitgeschichte. Sie charakterisiert sich sowohl als geschichtswissenschaftliche Forschungsmethode als auch Unterrichtsmethode zur Erstellung, Bearbeitung und Interpretation historischer Quellen mittels Erinnerungsinterviews zu vergangenen Erlebnissen und Erfahrungen (vgl. Michalik 2017, Schreiber 2009). Trotz einer bildungspolitischen Empfehlung der Methode der Zeitzeug*innenbefragung ab dem Anfangsunterricht des Sachunterrichts (vgl. u.a. Niedersächsisches Kultusministerium 2017), standen bislang im (inter-)nationalen Raum Studien, die die Zeitzeug*innenbefragung als didaktisches Arrangement historischen Lernens im Sachunterricht untersuchen sowie die Kinderperspektive auf die Methode der Zeitzeug*innenbefragung erfassen, aus. Entsprechend fokussiert die vorliegende, explorative und qualitativ angelegte Studie die Präkonzepte von Grundschulkindern zur Methode der Zeitzeug*innenbefragung. Mittels leitfadengestützter teilstandardisierter Einzelinterviews wurden die Präkonzepte zur Methode sowie zum Wissenschaftsverständnis bezüglich Zeitzeug*innen als historische Quelle rekonstruiert (vgl. Fuhs 2012, Helfferich 2011). Das Sample setzte sich aus Grundschulkindern der zweiten und vierten Klasse zusammen. Zur Bearbeitung und Auswertung des Datenmaterials diente eine in Anlehnung an die Lehr- und Lernforschung adaptierte Vorgehensweise der Qualitativen Inhaltsanalyse, die entsprechend modifiziert und erweitert wurde (vgl. Kuckartz 2018). Die Befunde der Studie zeigen differenzierte Präkonzepte der interviewten Zweit- und Viertklässler*innen zum Kontext der Methode der Zeitzeug*innenbefragung auf. Im Weiteren verweisen die Befunde darauf, dass die Zeitzeug*innenbefragung als Unterrichtsmethode ihre Legitimation im historischen Lernen mit Beginn des Anfangsunterrichts in der Grundschule hat.
Keywords: Präkonzepte; Zeitzeugenbefragung; Historisches Lernen; Sachunterricht; qualitative Forschung

Die Zeitzeugenbefragung aus der Sicht von Grundschulkindern - Diederich, Julia (Historisches Lernen in der Primarstufe. Standpunkte – Herausforderungen – Perspektiven)

Simmels Abhandlungen zu Kant - Luft, Sebastian (Simmel-Handbuch)

Cassirer’s Children, Special Topics Issue
Keywords: General Medicine

Wilhelm Windelband. Präludien

Graph-PIT: Generalized Permutation Invariant Training for Continuous Separation of Arbitrary Numbers of Speakers - von Neumann, Thilo; Kinoshita, Keisuke; Boeddeker, Christoph; Delcroix, Marc; Haeb-Umbach, Reinhold (Interspeech 2021)
Automatic transcription of meetings requires handling of overlapped speech, which calls for continuous speech separation (CSS) systems. The uPIT criterion was proposed for utterance-level separation with neural networks and introduces the constraint that the total number of speakers must not exceed the number of output channels. When processing meeting-like data in a segment-wise manner, i.e., by separating overlapping segments independently and stitching adjacent segments to continuous output streams, this constraint has to be fulfilled for any segment. In this contribution, we show that this constraint can be significantly relaxed. We propose a novel graph-based PIT criterion, which casts the assignment of utterances to output channels in a graph coloring problem. It only requires that the number of concurrently active speakers must not exceed the number of output channels. As a consequence, the system can process an arbitrary number of speakers and arbitrarily long segments and thus can handle more diverse scenarios. Further, the stitching algorithm for obtaining a consistent output order in neighboring segments is of less importance and can even be eliminated completely, not the least reducing the computational effort. Experiments on meeting-style WSJ data show improvements in recognition performance over using the uPIT criterion.
Keywords: Continuous speech separation; automatic speech recognition; overlapped speech; permutation invariant training

Speeding Up Permutation Invariant Training for Source Separation - von Neumann, Thilo; Boeddeker, Christoph; Kinoshita, Keisuke; Delcroix, Marc; Haeb-Umbach, Reinhold (Speech Communication; 14th ITG Conference)

Handling of explicit Uncertainty in Requirements Change Management - Gräßler, Iris; Pottebaum, Jens; Oleff, Christian; Preuß, Daniel (Proceedings of the Design Society)
Abstract Innovation projects are characterized by numerous uncertainties. Typical concepts in development management like the application of safety coefficients imply limitations of the solution space. In contrast, explicit handling of uncertainties can support engineers in understanding the problem space and in utilising the full potential of the design space along iterative product development steps. As a result from literature analysis, there is a lack of a support for product development that addresses the specific problem of uncertainty and risk in the context of requirement changes. The aim of the contribution at hand is to enhance the efficient development of complex interdisciplinary systems by enabling uncertainty handling in requirements change management. Based on a classification of uncertainty types resulting in a descriptive model, risk management measures are identified to support requirements engineers. The proposed method includes identification & modelling, analysis, treatment and monitoring of risks and counter-measures. By applying this method, engineers are supported in adopting agile approaches and enabling flexible Requirements Engineering.

Ein reaktiver Modellierungsansatz für Mensch-Roboter-Kollaboration in Rettungs- und Brandszenarien der Feuerwehr - Gürtler, Marius; Mandischer, Nils; Hüsing, Mathias; Corves, Burkhard; Pottebaum, Jens; Roesmann, Daniel; Gräßler, Iris (7. IFToMM D-A-CH Konferenz 2021; 18. - 19. Feb. 2021 IFToMM D-A-CH)

Fähigkeitsorientierte Aufgabenzuordnung für die Mensch-Roboter-Kollaboration in sicherheitskritischen Einsatzsituationen - Gräßler, Iris; Pottebaum, Jens; Roesmann, Daniel; Mandischer, Nils; Gürtler, Marius; Hüsing, Mathias; Corves, Burkhard (Mensch und Computer 2021 - Workshopband)

Model based Integration of Human Characteristics in Production Systems: A Literature Survey - Gräßler, Iris; Roesmann, Daniel; Pottebaum, Jens (14th CIRP Conference on Intelligent Computation in Manufacturing Engineering; 15. - 17. Jul. 2020)

Generic Product Lifecycle Model: A Holistic and Adaptable Approach for Multi-Disciplinary Product-Service Systems - Gräßler, Iris; Pottebaum, Jens (Applied Sciences)

Couleur Locale - Schulze, Max (Produktive Bildstörung: Sigmar Polke und aktuelle künstlerische Positionen)
Keywords: Sigmar Polke; Bildstörung; Camouflage; Wandfarbe

Friedrich Schneider, Christus das Kind. Oratorium in drei Teilen - Werbick, Regina; Höink, Dominik; Memering, Robert

CDS Investors’ Risk Perceptions of M&A Announcements - Hippert, Benjamin; Uhde, André
Merging a sample of 492 merger and acquisition (M&A) announcements from 284 acquiring firms across Europe and North America with data from 5-year single-name credit default swaps (CDSs) written on stock-listed acquiring firms between 2005 and 2018, the paper at hand empirically analyzes the CDS investors’ risk perceptions of M&A announcements using event study methodologies. As a baseline result, we provide evidence for significantly positive cumulative average abnormal CDS spread changes for both, European and North American acquirers suggesting that CDS investors perceive an increase in the acquiring firms’ credit risk exposures due to M&A announcements. Our baseline finding holds under several robustness checks, especially when controlling for the robustness of the empirical design. Moreover, results from a large variety of sensitivity analyses reveal a number of deal and firm characteristics that may explain why CDS investors from our sample expect an increase in the acquirers’ credit risk exposures due to forthcoming M&A transactions.
Keywords: credit default swaps; risk perception of CDS investors; mergers and acquisitions; event study

Determinants of CDS Trading on Major Banks - Hippert, Benjamin; Uhde, André; Wengerek, Sascha Tobias
This paper empirically investigates determinants of the outstanding net notional amount of credit default swaps (CDSs) contracts written on banks. We extend and complement the previous literature dealing with CDS trading by analyzing a comprehensive set of CDS tradingspecific, bank-fundamental, macroeconomic and bank-institutional determinants. We find that risk hedging clearly dominates an investor’s speculation and arbitrage motive, while the latter, however, exhibits the strongest impact on the outstanding net notional amount of bank CDSs. Furthermore, being classified as a G-SIB, being a constituent of the main CDS index and the equity trading volume may significantly explain changes in the outstanding CDS net notional on banks. The analysis at hand provides important implications for both academics and practitioners, since understanding the trading motives of bank CDS investors provides a deeper insight into the opaque CDS market.
Keywords: banking; outstanding CDS net notional; determinants of bank CDS trading

Der Wunsch zu verschwinden - Schulze, Max
Das Buch stellt die drei jüngeren Serien Cool Mild Pure Warm (Streetfile), EPS und Der Wunsch zu verschwinden (Camopedia) des Künstlers Max Schulze vor. Ihm geht es um die Frage, an welchen Orten und auf welche Weise Malerei im Jahr 2021 entsteht: Wie sieht es mit den althergebrachten Kategorisierungen von Farbe und Form, Figuration und Abstraktion oder Fläche und Raum aus? Welche Wege sucht sich vor diesem Hintergrund die heutige Malerei und welche ästhetische Kraft ist ihr eigen? Die 32 Bilder der Serie Der Wunsch zu verschwinden (Camopedia) basieren auf den 32 Farbtönen des Systems «Alpina Feine», die Schulze verwendet, um unterschiedliche Camouflage-Muster zu malen. Dieses speziell kuratierte Farbsystem wird aus Marketinggründen mit Wohlfühlassoziationen verbunden. Diese Aufladung crasht mit der Verwendung des Tarnmusters im militärischen Bereich. Schulze beschäftigt die Frage, warum gerade heute, in einer Zeit, die von vielen politischen und sozialen Veränderungen bestimmt ist, Camouflage in Mode und Design allgegenwärtig ist. Für die Serie Cool Mild Pure Warm (Streetfile) greift Schulze ebenfalls auf Farbsysteme zurück, die er mit Fotos von diversen Farb-Attentaten im öffentlichen Raum kombiniert. So entsteht ein – nicht ganz humorloser – Kommentar zur kommerziellen Nutzung von Farbe in Farbsystemen, aber auch zu deren Zweckentfremdung durch politische «Attacken» im öffentlichen Raum. Der Name der Serie EPS bezieht sich auf ein Material, das unter dem Markennamen Styropor bekannt ist. Schulze klebt es auf abstrakte Malereien, doch nicht vollständig, sondern so, dass Teilbereiche der darunter liegenden Bildebene frei bleiben. Das darunter liegende Bild wird gleichsam verdeckt wie durch die Dämmung geschützt. Es entsteht ein ähnlich ambivalenter Seh-Eindruck wie bei den anderen Serien.
Keywords: Camouflage; Malerei; Wandfarbe; Wohlfühlstrategien; Farbsysteme; Farb-Attentat; öffentlicher Raum; Dämmung; Zwecketfremdung

Self-Trained Audio Tagging and Sound Event Detection in Domestic Environments - Ebbers, Janek; Haeb-Umbach, Reinhold (Proceedings of the 6th Detection and Classification of Acoustic Scenes and Events 2021 Workshop (DCASE2021))
In this paper we present our system for the Detection and Classification of Acoustic Scenes and Events (DCASE) 2021 Challenge Task 4: Sound Event Detection and Separation in Domestic Environments, where it scored the fourth rank. Our presented solution is an advancement of our system used in the previous edition of the task.We use a forward-backward convolutional recurrent neural network (FBCRNN) for tagging and pseudo labeling followed by tag-conditioned sound event detection (SED) models which are trained using strong pseudo labels provided by the FBCRNN. Our advancement over our earlier model is threefold. First, we introduce a strong label loss in the objective of the FBCRNN to take advantage of the strongly labeled synthetic data during training. Second, we perform multiple iterations of self-training for both the FBCRNN and tag-conditioned SED models. Third, while we used only tag-conditioned CNNs as our SED model in the previous edition we here explore sophisticated tag-conditioned SED model architectures, namely, bidirectional CRNNs and bidirectional convolutional transformer neural networks (CTNNs), and combine them. With metric and class specific tuning of median filter lengths for post-processing, our final SED model, consisting of 6 submodels (2 of each architecture), achieves on the public evaluation set poly-phonic sound event detection scores (PSDS) of 0.455 for scenario 1 and 0.684 for scenario as well as a collar-based F1-score of 0.596 outperforming the baselines and our model from the previous edition by far. Source code is publicly available at https://github.com/fgnt/pb_sed.